THE EFFECT OF PROJECT BASED LEARNING (PjBL) ON STUDENTS' UNDERSTANDING AND CREATIVITY IN LEARNING GLOBAL WARMING CONCEPT - Umam, Ahmad Zimamui (2013)
This research investigated the effect of project based learning (PjBL) on students' understanding and creativity in learning global warming concept. The method which is used in this research was combination of pre experimental and descriptive with one group pretest-posttest design. The sample was taken purposively (n=19 students) grade secondary 1 in a Private International School. The quantitative data of this research was obtained through objective test, while the qualitative data was gained through rubric and questionnaire. According to the analysis of the research, it is obtained an improvement in both students' understanding and creativity. Students' understanding improvement obtained normalized gain as much as 0.61 which is categorized into medium improvement. The students' creativity is shifting. Before project based learning being implemented it was in enough categories and changed into good category in the end. It shows that project based learning can facilitate students to explore their creativity. The improvement occurred in all creativity dimensions that are novelty, resolution, and elaboration & synthesis. Students' respond toward implementation of project based learning showed positive respond in all indicators. It indicates that the implementation of project based learning in global warming concept can improve students' understanding and creativity in secondary level.